2014
DOI: 10.1159/000357420
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Thrombus Attenuation on Thin-Slice Non-Contrast CT for Persistent Occlusion after Intravenous Thrombolysis

Abstract: Background: In stroke erythrocyte-rich thrombi are more sensitive to intravenous thrombolysis with recombinant tissue plasminogen activator (IV-rtPA) and have higher density on non-contrast CT (NCCT). We investigated the relationship between thrombus density and recanalization and whether persistent occlusions can be predicted by Hounsfield unit (HU) measurements. Methods: In 88 IV-rtPA-treated patients with intracranial ICA or MCA occluding thrombus and follow-up imaging, thrombus and contralateral vessel att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…However, it is only effective in less than half of the patients that receive rt-PA. 2,3 The mechanisms underlying this so called "rt-PA-resistance" are not completely understood but previous reports indicated that RBC-dominant thrombi respond better to rt-PA than platelet-dominant thrombi. [18][19][20][21][22][23][24][25][26] Our histological findings provide new molecular insights on the composition of RBC-rich and platelet-rich thrombus material. It seems plausible that rt-PA, which promotes the degradation of fibrin, can have a direct and efficient thrombolytic effect on the RBC-rich areas in which thin fibrin is the main extracellular scaffold.…”
Section: Discussionmentioning
confidence: 79%
“…However, it is only effective in less than half of the patients that receive rt-PA. 2,3 The mechanisms underlying this so called "rt-PA-resistance" are not completely understood but previous reports indicated that RBC-dominant thrombi respond better to rt-PA than platelet-dominant thrombi. [18][19][20][21][22][23][24][25][26] Our histological findings provide new molecular insights on the composition of RBC-rich and platelet-rich thrombus material. It seems plausible that rt-PA, which promotes the degradation of fibrin, can have a direct and efficient thrombolytic effect on the RBC-rich areas in which thin fibrin is the main extracellular scaffold.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, the inverse correlation of VWF presence with red blood cell content in the thrombus is particularly interesting because radiological imaging on admission was shown to predict thrombus red cell content. 6,44 Determining thrombus composition from radiological signs may help identify patients who could benefit from specific thrombolytic approaches such as the use of ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
“…They therefore had suspected stroke and an indication for ­IV-rtPA. Moreover, the detection of ischemia on CT perfusion is not 100%; small infarcts and infarcts outside the scan range can be missed [27]. Since this is true for the entire study population, it should not have influenced the analyses.…”
Section: Discussionmentioning
confidence: 99%